2016
DOI: 10.1007/s00464-016-4897-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of large hiatus hernia: five-year cohort study and comparison of mesh-augmented versus standard crura repair

Abstract: Laparoscopic repair of large hiatal hernia is effective and durable. Crura reinforcement with a resorbable synthetic mesh is safe and may protect from early anatomical recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 20 publications
0
23
0
2
Order By: Relevance
“…Closing hiatus routinely can reduce this complication by upto 80% [11]. Closing large hiatuses with grafts has been reported to prevent recurrences [12,13]; however, complications such as migration into lumen can be experienced with graft use [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closing hiatus routinely can reduce this complication by upto 80% [11]. Closing large hiatuses with grafts has been reported to prevent recurrences [12,13]; however, complications such as migration into lumen can be experienced with graft use [14].…”
Section: Discussionmentioning
confidence: 99%
“…Biological meshes have been developed against organ resection and loss that occurs secondary to mesh erosion [22]. It has been stressed that mesh problems that have been reported to occur at a low rate do not constitute any major contraindication for mesh use [13]. Mesh fixation can be accomplished with various different materials including sutures, metal fixators and glues [23].…”
Section: Discussionmentioning
confidence: 99%
“…There are two statements on it in the guidelines. One is, “The use of mesh for reinforcement of large hiatal hernia repairs leads to decreased short‐term recurrence rates.” Although mesh involves complications, it reduces short‐term recurrence rates . The other statement is, “There are inadequate long‐term data on which to base a recommendation either for or against the use of mesh at the hiatus.” Recently, a report using the data from a period of 48 months following surgery indicated that the use of mesh decreased the recurrence rate.…”
Section: Outcomes Of Surgery Treatment For Lhhmentioning
confidence: 99%
“…In addition, the suture and tacking during mesh fixation may involve serious complications such as cardiac tamponade. Recently, there have been fewer reports on serious complication compared to the past . It has also been reported that not using prosthesis mesh resulted in a low recurrence rate and good treatment outcomes …”
Section: Outcomes Of Surgery Treatment For Lhhmentioning
confidence: 99%
“…Some studies seem to encourage mesh placement mainly due to decreased short-term recurrence rates compared to suture hiatal repair [17][18][19]. Others suggest that primary crural repair with or without mesh reinforcement, does not alter the recurrence rate and the five-year recurrence-free probability is similar in both groups [20]. The limited available information does not allow us to make conclusions about the longterm efficacy of mesh in this setting.…”
Section: Editorialmentioning
confidence: 99%